Encyclopedia of global studies - Anheier, Helmut K. (SAGE, 2012)
This title covers both transnational topics and intellectual approaches to the study of global themes, including: the globalization of economies and technologies; the diaspora of cultures and dispersion of peoples; the transnational aspects of social and political change; the global impact of environmental, technological and health changes; and the organizations and issues related to global civil society.
Keywords: Wörterbuch; Globalisierung